A new route to quinolone and indole skeletons via ketone- and ester-imide cyclodehydration reactions - Kim, G; Keum, G (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
Ketone-imide cyclodehydration reactions of aromatic succinimide and phthalimide (7, 8) have afforded quinolone acids (11, 12). Further transformation of the acids provided the corresponding esters (13, 14) and vinylogous urethanes (9, 10). Similarly, ester-imide cyclodehydration reactions of aromatic imide esters (19, 20) have afforded indole acids (23, 24).
Keywords: TOPOISOMERASE-II; CYCLOARACYLATION; IDENTIFICATION; CYTOTOXICITY; ENAMINES; ACIDS